36=-2(22-m)+4(m-4)

Simple and best practice solution for 36=-2(22-m)+4(m-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=-2(22-m)+4(m-4) equation:


Simplifying
36 = -2(22 + -1m) + 4(m + -4)
36 = (22 * -2 + -1m * -2) + 4(m + -4)
36 = (-44 + 2m) + 4(m + -4)

Reorder the terms:
36 = -44 + 2m + 4(-4 + m)
36 = -44 + 2m + (-4 * 4 + m * 4)
36 = -44 + 2m + (-16 + 4m)

Reorder the terms:
36 = -44 + -16 + 2m + 4m

Combine like terms: -44 + -16 = -60
36 = -60 + 2m + 4m

Combine like terms: 2m + 4m = 6m
36 = -60 + 6m

Solving
36 = -60 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
36 + -6m = -60 + 6m + -6m

Combine like terms: 6m + -6m = 0
36 + -6m = -60 + 0
36 + -6m = -60

Add '-36' to each side of the equation.
36 + -36 + -6m = -60 + -36

Combine like terms: 36 + -36 = 0
0 + -6m = -60 + -36
-6m = -60 + -36

Combine like terms: -60 + -36 = -96
-6m = -96

Divide each side by '-6'.
m = 16

Simplifying
m = 16

See similar equations:

| -23=n+11 | | -16-5n=-7(-6+8n)+3 | | 35-(x-1)=-7(5-x)+28x | | -8x+-12=-44 | | 6x-9=6(x+7) | | 6/b-1=9/1 | | 6x+36/35x+20/3x+18/7x+4 | | 2(x+3)=8(x-2)-2 | | N-13+6=8 | | -16-5n=(-6+8n)+3 | | 3x-5+2=20 | | -9+12x=75 | | -25+7x-4x=53 | | (4p^-5/p^5)^3 | | x-6=4x+3 | | 4y+17=3y-26 | | 10b-5b=55 | | 6+2p-2=8p+14-4p | | 5x-18=63 | | x/-5=17 | | 7m-77-16m-60=28 | | 2-5y=14 | | 8(t-4)+7t=(3t-3)-12 | | 9+7x=-68 | | 7(h+3)=2(6m+8) | | 1/4x-2/3y=8 | | 10x-(9x-6)=10 | | 1/9*9w | | 3(4z+2)-7=95 | | 4x+3/12+x-3/2=3x+1/4 | | 3/4(2x-6)=1/2x-4 | | 3(5h-12)=9 |

Equations solver categories